Mannanase and Cellulase Enzyme Production from the Agricultural Wastes by the Bacillus subtilis P2-5 Strain - Pangsri, Prapawan; Wuttipornpun, Teeradej; Songserm, Watchara (Applied Science and Engineering Progress, 2021)
The objective of this research was to use agricultural wastes as substrates in enzyme production processes, instead of using a commercial substrate named locust bean gum (LBG), in order to determine an alternative way of managing agricultural wastes, to reduce waste disposal costs, and to reduce enzyme production costs. There are four potential factors generally considered in enzyme production, which are designated as a substrate, an inoculum, temperature, and an incubator shaker speed. In this research, three agricultural wastes, namely tea waste, coffee grounds, and copra meal were considered as substrates. A new bacterium that was isolated from the soil named Bacillus subtilis P2-5 was considered as the inoculum, and it was tested at 1 and 5% (v/v). A factorial experiment was then conducted, in order to study the effects of these factors and their interactions on mannanase and cellulase activities. The results showed that the three wastes can be used as substrates to produce mannanase and cellulase. Tea waste obtained the highest enzyme activities when compared to coffee grounds and copra meal. The optimal condition to maximize both of the mannanase and cellulase activities was to use tea waste, 1% (v/v) of inoculum, 37°C, and 150 rpm. Although the enzyme activities obtained from the tea waste were lower than those obtained from LBG, the proposed idea is still recommended, since benefits from these agricultural wastes can be obtained, rather than merely casting them aside.